Membangun Generasi Cerdas Digital Kolaborasi Manusia dan AI Dalam Dunia Pendidikan - Liza Yulianti; Reno Supardi; Asnawati Asnawati; Karien Eka Putri; Muhammad Davit Alexsander (Jurnal Dehasen Mengabdi, 2026)
The development of digital technology and artificial intelligence has significantly impacted the field of education. However, several challenges remain in implementing digital technology in schools, including low digital literacy, limited understanding of Artificial Intelligence (AI), and insufficient skills among teachers and students in utilizing technology effectively. This community service activity aimed to improve the understanding and skills of students and teachers regarding the collaboration between humans and AI in supporting learning processes. The implementation methods included observation, counseling, training, interactive discussions, and evaluation activities. The program was conducted at SMA Negeri 10 Kabupaten Seluma involving teachers and students as the main participants. The results showed an increase in participants’ understanding of the use of AI in education, greater awareness of responsible technology use, and improved student motivation in utilizing digital technology to support learning activities. Collaboration between humans and AI in education can create a more adaptive, interactive, and effective learning process that supports the formation of a creative, innovative, and ethical digital generation.